Interpreting the Death and Ascension of Prophet Isa a.s. in the Qur’an: A Comparative Study of al-Tabari and al-Alusi - Cindy Romadona (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
The interpretation of the death and ascension of Prophet Isa in the Qur’an remains a debated issue in Islamic exegesis, particularly regarding the meaning of tawaffā and the role of transmitted and rational sources in interpretation. Differences in exegetical approaches among classical scholars highlight the need for a critical and comparative analysis of their interpretive methods and sources. This study aims to analyze Qur’anic verses related to the death and ascension of Prophet Isa and to compare the interpretive approaches of al-Ṭabarī and al-Ālūsī. The research employs a qualitative library approach using thematic analysis and content analysis. It also applies sanad criticism within the framework of al-dakhīl fī al-tafsīr to evaluate the validity of transmitted reports. The findings show that the relevant verses include Q. 3:55, Q. 4:157–158, Q. 5:117, and Q. 19:33. The sources of interpretation in both tafsīr works consist of tafsīr bi al-ma’thūr, tafsīr bi al-ra’y, and isrā’īliyyāt. Both al-Ṭabarī and al-Ālūsī interpret tawaffā as the taking of Prophet Isa from the earth and his ascension to heaven. However, they differ methodologically: al-Ṭabarī strengthens his interpretations through Qur’anic cross-references, hadith, and companions’ opinions, while al-Ālūsī emphasizes linguistic and rational analysis. The study also finds that the isrā’īliyyāt narrations used are considered acceptable insofar as they align with Islamic teachings. This study contributes to understanding the diversity of classical tafsīr methodologies and highlights how different epistemological approaches shape interpretations of key theological issues.